Venomous snakebites: Rapid action saves lives-A multifaceted community education programme increases awareness about snakes and snakebites among the rural population of Tamil Nadu, India. - Stephen Paul Samuel (PLoS Neglected Tropical Diseases, 2020)
The lack of public awareness surrounding the dangers of snakebite envenomation (SBE) is one of the most critical factors contributing to SBE-induced complications, and subsequently exacerbating the number of deaths and disabilities resulting from SBE. In this study, we deployed a multifaceted community education programme to educate students, healthcare professionals and members of the public in rural areas of Tamil Nadu, India about the dangers of SBE, appropriate first aid measures and the 'do's and don'ts' following a snakebite. An assessment of prior knowledge within these communities identified several misconceptions concerning snakes and SBE. Using a combination of direct engagement (estimated to reach over 200,000 people), information leaflets (200,000 distributed), posters, video documentaries, media and social media (>2.8 million engagements), over the course of one year (January to December 2019) we reached over 3 million people in rural Tamil Nadu (around 8% of population). Evaluation of community-based assemblies indicated that at least 90% of attendees were able to recall the key messages at the end of the events, and at least 85% were able to recall the key messages even after 12 months. Due to high demand, a one-day symposium was organised to provide clinical knowledge and training on SBE to 250 healthcare professionals in rural Tamil Nadu. Notably, an assessment of patient data (291 victims) collected from a snakebite referral hospital over the same 12-month period (2019) indicated that arrival time at hospital following a snakebite was significantly faster and the effective first aid measures were administered to patients who were aware of our activities compared to those that were not. Overall, our approach provides a framework on how to educate rural communities about the dangers of SBE and thereby, mitigate delayed SBE treatment leading to an overall reduction in SBE-induced mortality, morbidity, treatment costs and other socio-economic ramifications.